How to structure a thesis, report or paper a guide for students - Ormrod, Robert P. (London Routledge, 2023)
How to Structure a Thesis, Report or Paper provides concise practical guidance for students to help make their writing more structured at any level. It assists students in demonstrating what they have learned in the relevant course or degree programme in a way that is accessible to the supervisor and the examiner.Drawing on almost 20 years of supervision experience, the author presents the eight sections of a well-structured thesis, report or paper, together with discussing other relevant issues. Each chapter provides a detailed description of why each section of a thesis, report or paper is structured in the way it is, and its relationship to the whole piece of work. Good and bad examples are provided throughout the book, and there is a focus on key areas such as the six parts of an Introduction and its relationship to the Conclusion, how to phrase clear research questions and hypotheses to the use of references and how to make the thesis, report or paper easier to read. The structure presented in this book can be used to support many courses on the student's entire degree programme, as the structure can be adapted by re-arranging or deleting sections.This book is an invaluable aid to students at all stages in higher education, from their first report or paper until they write their final thesis. It provides clear guidelines for when students should ask their supervisors for advice, and when students can use their own initiative to learn the most. It makes writing a thesis, report or papers more straightforward!
How to structure a thesis, report or paper -- The introduction -- Literature review -- Methodology and method -- Quantitative investigations: results and analysis -- Qualitative investigations: findings and discussion -- Reflections: implications, limitations and suggested future research directions -- The conculsion - and the introduction revisited -- References and the bibliography -- Hygiene factors Alternative thesis, report and paper structures, and the oral defence -- How to structure a thesis, report or paper -- Finished! Sort of.. -- Epilogue.
Keywords: Dissertations, Academic